1997
DOI: 10.1115/1.2829055
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Affected Zone Toughness of a TMCP Steel Designed for Low-Temperature Applications

Abstract: The objective of this investigation was to provide a detailed evaluation of the heat-affected zone (HAZ) toughness of a high-strength TMCP steel designed for low-temperature applications. The results from both Charpy-vee notch (CVN) and cracktip-opening displacement (CTOD) tests conducted on two straight-walled narrow groove welds, produced at energy inputs of 1.5 and 3.0 kJ/mm, show that significantly lower toughness was exhibited by the grain-coarsened HAZ (GCHAZ) compared with the intercritical HAZ (ICHAZ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…[5,30] It is worth noting that the conventional definitions of the HAZ microstructure, primarily in low alloy steel welds, involves a further classification of the regions with a peak temperature above the Ac 3 temperature into the so-called coarse-grain and fine-grain regions, related to whether the grain structure was significantly influenced by second-phase particles. [1,2,14] However, it was observed in this case that the rapid weld thermal cycle results in the Ac 3 temperature being close to the temperature at which the pre-existing secondary precipitates are completely dissolved. Thus, although some variation in the grain structure in the regions that were heated above the Ac 3 temperature was observed (Figures 20 and 21), this was primarily a function of distance from the weld line, rather than being caused by the presence of undissolved secondary precipitates.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…[5,30] It is worth noting that the conventional definitions of the HAZ microstructure, primarily in low alloy steel welds, involves a further classification of the regions with a peak temperature above the Ac 3 temperature into the so-called coarse-grain and fine-grain regions, related to whether the grain structure was significantly influenced by second-phase particles. [1,2,14] However, it was observed in this case that the rapid weld thermal cycle results in the Ac 3 temperature being close to the temperature at which the pre-existing secondary precipitates are completely dissolved. Thus, although some variation in the grain structure in the regions that were heated above the Ac 3 temperature was observed (Figures 20 and 21), this was primarily a function of distance from the weld line, rather than being caused by the presence of undissolved secondary precipitates.…”
Section: Discussionmentioning
confidence: 90%
“…Compared with the existing definition of the HAZ microstructure in 9 wt pct Cr steel welds, [1,2,14] the ranges of the corresponding peak temperatures of these two regions are close to the so-called intercritical and so-called overtempered (OT) regions, respectively. However, the terminology intercritical does not clearly indicate the fact that not only the martensitic matrix was partially reaustenitized but also the secondary precipitates in the original matrix were affected by weld thermal cycles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5, plays an important role in regards to the HAZ Charpy impact testing. According to Gianetto et al (1997) as the width of the HAZ is growing, with increased heat input, the impact energy for the fusion line is reduced According to Fig. 11(b) at the fusion line region, the highest absorbed energy of about 40 J was obtained in specimen 7, which was welded with a total heat input of 6 kJ/mm.…”
Section: Resultsmentioning
confidence: 97%
“…The austenite grain in the HAZ is considerably coarser when compared to the grain size of the parent metal. Gianetto et al (1997) have reported the extent of the austenite grain growth is dependent upon the weld thermal cycle, the steel composition and the precipitate chemistry. In order to prevent brittle fracture, excellent low-temperature toughness is required in the base metal and the HAZ of a pipeline's welded joint.…”
Section: Introductionmentioning
confidence: 98%